Can serum procalcitonin be used to direct antibiotic therapy in outpatients with acute respiratory infections?. Issue 7 (July 2015) - Bersanti, Kira; Colson, Emily
Abstract : Evidence‐based answer : Yes. In the outpatient management of acute respiratory infections, serum procalcitonin use reduces patient exposure to antibiotics without any decrease in treatment success (SOR: A, consistent RCTs).